CERAI GUGAT DI KOTA CILEGON - Agus Mulyono (Harmoni, 2017)
This research focuses on the phenomenon of cerai gugat (divorce sued by wife) in Cilegon town. Based on the qualitative approach, this research has conducted deep interview as data collection method with women sueing divorce, officers within Religious Court and Ministry of Religious Affairs, as well as public religious figures in Cilegon.The socio-economic circunstance of Cilegon society is influential to the patterns of divorce. The divorces are strongly linked to the readiness to face modernity. Economy as one of important variables of modern society has become one of the problems of divorce. Cilegon osciety is categorised as a semi-modern society as Cilegon is one of the centres of government and economic movement. The society must adapt themselves with the context social change which mostly determines and creates them to have pragmatic and realistic orientation of life. They would maintain their life as long as they survive and enjoy life within modernity. The contrary will happen otherwise. If they could establish and exist in the context of social change, they would survive and maintain their family household. Otherwise, divorce is an alternative.